Biological functions and applications of LncRNAs in the regulation of the extracellular matrix in osteoarthritis - Shi, Di; Mei, Yufeng; Hao, Wan; Li, Jun; Liu, Shuguang; Lin, Xiao (Frontiers in Cell and Developmental Biology, 2024)
Osteoarthritis (OA) is a major cause of disability, characterized by chronic pain, irreversible destruction, and loss of function of the articular cartilage. The integrity and arrangement of the composition and structure of the extracellular matrix (ECM) are essential for maintaining the elasticity, integrity, and mechanical support function of the cartilage tissue. Osteoarthritis causes substantial changes in the ECM, driving the progression of the disease. Recent studies have shown that the ECM plays a critical role in the development of cartilage tissue as well as the occurrence and development of osteoarthritis by directly or indirectly regulating chondrocyte proliferation, apoptosis, differentiation, and gene expression. Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs derived from large transcripts. Mutations and disorders of lncRNAs are closely related to the development of osteoarthritis. Abnormal expression of lncRNAs in osteoarthritic cartilage regulates the synthesis and decomposition of the cartilaginous ECM. Therefore, the use of lncRNAs as nucleic acid drugs that regulate their targets may reduce ECM degradation, thereby delaying the pathological progression of osteoarthritis. In this review, the regulatory effects of lncRNAs on ECM in different cell behaviors related to OA are summarized. The roles of lncRNAs in the proliferation, apoptosis, differentiation, and ECM-related gene activity of chondrocytes, as well as the application of lncRNAs as potential gene therapy drugs for the repair and regeneration of osteoarthritic tissue, are also reviewed. A better understanding of the roles of lncRNAs in guiding chondrocyte behavior and ECM metabolism is critical for their future applications in osteoarthritis therapy and regenerative medicine.